(untitled) - Jordan B. Peterson (New York Portfolio/Penguin, 2021)
The sequel to 12 Rules for Life offers further guidance on the periolus path of modern life. In 12 Rules for Life, clinical psychologist and celebrated professor at Harvard and the University of Toronto Dr. Jordan B. Peterson helped millions of readers impose order on the chaos of their lives. Now, in this bold sequel, Peterson delivers twelve more lifesaving principles for resisting the exhausting toll that our desire to order the world inevitably takes. In a time when the human will increasingly imposes itself over every sphere of life-from our social structures to our emotional states-Peterson warns that too much security is dangerous. What's more, he offers strategies for overcoming the cultural, scientific, and psychological forces causing us to tend toward tyranny, and teaches us how to rely instead on our instinct to find meaning and purpose, even-and especially-when we find ourselves powerless. While chaos, in excess, threatens us with instability and anxiety, unchecked order can petrify us into submission. Beyond Order provides a call to balance these two fundamental principles of reality itself, and guides us along the straight and narrow path that divides them.
Keywords: Nonfiction; Philosophy; Psychology; Self Help